Selective Production of Oxygenates from Carbon Dioxide Hydrogenation over a Mesoporous‐Silica‐Supported Copper‐Gallium Nanocomposite Catalyst. Issue 6 (16th February 2018) - Hengne, Amol M.; Bhatte, Kushal D.; Ould‐Chikh, Samy; Saih, Youssef; Basset, Jean Marie; Huang, Kuo‐Wei
Abstract: The hydrogenation of CO2 to oxygenates (methanol and dimethyl ether; DME) was investigated over bifunctional supported Cu catalysts promoted with Ga. The supported Cu‐Ga nanocomposite catalysts were characterized by using XRD, TEM with energy dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and H2 temperature‐programmed reduction. In comparison with Cu‐SBA‐15‐based catalysts, the Ga‐promoted catalyst prepared by the urea deposition method (Cu‐Ga/SBA‐15‐UDP) was more active and selective for CO2 hydrogenation to oxygenates. The use of Ga as the promoter led to increased acidic sites, which was confirmed by using NH3 temperature‐programmed deposition and IR spectroscopy with pyridine and 2, 6‐lutidine as probe molecules. The favorable effect of Ga on the CO2 conversion and selectivity to oxygenates may come from the strong interaction of Ga with silica, which is responsible for the enhanced metal surface area, the formation of the nanocomposite, and the metal dispersion. Notably, the incorporation of Ga into Cu/SiO2 led to a several‐fold higher rate for methanol formation (13.12 μmol gCu −1  s −1 ) with a reasonable rate for DME formation (2.15 μmol gCu −1  s −1 ) compared to Cu/SiO2 catalysts. Abstract : Ga‐reat with gallium : We describe the single‐step conversion of CO2 to oxygenates (methanol and dimethyl ether) over a SiO2 ‐supported Cu‐Ga bifunctional catalyst.